2019
DOI: 10.3390/f10060468
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Natural Evergreen Broadleaved Forests Decreases Soil Organic Carbon but Increases the Relative Contribution of Microbial Residue in Subtropical China

Abstract: It has been recognized that land use change affects soil organic carbon (SOC) dynamics and the associated microbial turnover. However, the contribution of microbial residue to SOC storage remains largely unknown in land use change processes. To this end, we adopted a “space for time” approach to examine the dynamics of SOC and amino sugars, which was a biomarker of microbial residue C, in different natural forest conversions. Three typical converted forests were selected: an assisted natural regeneration (ANR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…For the deforested sites, the lowest values of microbial carbon biomass and microbial respiration correspond to the lowest abundance of labile and microbial-derived compounds [ 43 ]. This finding is consistent with the work done by Yang et al [ 44 ] and Zhou et al [ 45 ], who reported similar trends in the chemodiversity of DOM influenced by environmental factors [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…For the deforested sites, the lowest values of microbial carbon biomass and microbial respiration correspond to the lowest abundance of labile and microbial-derived compounds [ 43 ]. This finding is consistent with the work done by Yang et al [ 44 ] and Zhou et al [ 45 ], who reported similar trends in the chemodiversity of DOM influenced by environmental factors [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is generally considered that fungal residues are more difficult to decompose than bacterial residues; therefore, the primary reason for the decrease in the ratio of GluN/MurA in the warming treatment was the changes in microbial community structure (Yang et al, 2019). Besides, increased precipitation can change the community structure of microorganisms, and 220 the increases of soil moisture can make the bacterial-dominated soil microbial community structure evolve toward the fungus-dominated structure.…”
Section: Distribution and Turnover Patterns Of Amino Sugars In Alpine...mentioning
confidence: 99%
“…A large number of Land 2022, 11, 295 2 of 15 studies have examined the effects of forest conversion on important ecosystem services and processes [5][6][7]. The conversion of natural forests to forest plantations often causes soil degradation [8][9][10], especially the decline of nitrogen (N) availability [11][12][13]. Nitrogen is a common limiting nutrient element for ecosystem productivity [14] and is available to plants mainly in inorganic form (i.e., NH 4 + and NO 3 − ) in the soil.…”
Section: Introductionmentioning
confidence: 99%